2020
DOI: 10.1038/s41598-020-73556-5
|View full text |Cite
|
Sign up to set email alerts
|

Free circulating mircoRNAs support the diagnosis of invasive aspergillosis in patients with hematologic malignancies and neutropenia

Abstract: Fungal infections represent a worrisome complication in hematologic cancer patients and in the absence of disease specific symptoms, it is important to establish new biological indicators, which can be used during mould-active prophylaxis. Recently, miRNAs have appeared as candidate diagnostic and prognostic markers of several diseases. A pilot clinical study was performed to evaluate the diagnostic utility of 14 microRNAs which can be related to invasive fungal infections. Based on our data miR-142-3p, miR-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…In a study (Tab. 3), a significant association was confirmed between invasive aspergillosis and miRNAs, miR-142-3p, -142-5p, -26b-5p and miR-21-5p (Tolnai et al, 2020). A research identified 23 miRNAs that were associated with invasive pulmonary aspergillosis (IPA), a severe opportunistic infection caused by A. fumigatus with high mortality in patients with compromised immunity (Chen et al, 2019).…”
Section: Tlr4 Tlr9mentioning
confidence: 96%
“…In a study (Tab. 3), a significant association was confirmed between invasive aspergillosis and miRNAs, miR-142-3p, -142-5p, -26b-5p and miR-21-5p (Tolnai et al, 2020). A research identified 23 miRNAs that were associated with invasive pulmonary aspergillosis (IPA), a severe opportunistic infection caused by A. fumigatus with high mortality in patients with compromised immunity (Chen et al, 2019).…”
Section: Tlr4 Tlr9mentioning
confidence: 96%
“…Vast majority of the identified 33 miRNAs that regulate genes related to the pathogenesis of invasive aspergillosis (such as S100B, TDRD9 and TMTC1) were also linked to the finetuning of platelet activation [90]. Overexpression of miR-21-5p, miR-26-5p, miR-142-3p and miR-142-5p in cases of invasive aspergillosis in hemato-oncology patients with profound neutropenia may be applied as a promising diagnostic adjunct with sufficient accuracy and sensitivity [79].…”
Section: Mirna Fingerprints In Fungal Infectionsmentioning
confidence: 99%
“…But in a clinical study among hemato-oncology patients with profound neutropenia, free circulating miR-142-3p was significantly upregulated because of invasive aspergillosis. The reason for this difference may be related to the type of diseases [70].…”
Section: Perioperative Precision Medicinementioning
confidence: 99%